2020
DOI: 10.1093/mnras/staa3886
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the HD 21749 planetary system with stellar activity modelling

Abstract: HD 21749 is a bright (V = 8.1 mag) K dwarf at 16 pc known to host an inner terrestrial planet HD 21749c as well as an outer sub-Neptune HD 21749b, both delivered by Transiting Exoplanet Survey Satellite (TESS). Follow-up spectroscopic observations measured the mass of HD 21749b to be 22.7 ± 2.2 M⊕ with a density of $7.0^{+1.6}_{-1.3}$ g cm−3, making it one of the densest sub-Neptunes. However, the mass measurement was suspected to be influenced by stellar rotation. Here, we present new high-cadence PFS RV data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 86 publications
5
9
0
Order By: Relevance
“…We conducted our own analysis of the HD 21749 RVs as reported by Dragomir et al (2019) and found agreement in the mass measurement for the superdense sub-Neptune HD 21749 b between a model of the RVs with and without a GP trained on stellar activity indicators. We also found agreement between our measurements and the results of Gan et al (2021), who used a larger RV data set in addition to a GP model of the stellar activity signal. Details and results of our analysis are found in Appendix.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We conducted our own analysis of the HD 21749 RVs as reported by Dragomir et al (2019) and found agreement in the mass measurement for the superdense sub-Neptune HD 21749 b between a model of the RVs with and without a GP trained on stellar activity indicators. We also found agreement between our measurements and the results of Gan et al (2021), who used a larger RV data set in addition to a GP model of the stellar activity signal. Details and results of our analysis are found in Appendix.…”
Section: Discussionsupporting
confidence: 84%
“…Details and results of our analysis are found in Appendix. While the mass measurements for HD 21749 b agree between our two models (and both agree with the results in Dragomir et al 2019 andGan et al 2021), the GP-enabled model is heavily favored by the AIC (ΔAICc > 30) and produces a lower rms scatter in the residuals (Δrms > 2.5 m s −1 ). Overall, we find no evidence that unmitigated stellar activity can explain the high mass measurements of the superdense sub-Neptunes.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although thousands of large sub-Neptunes (2.75 R ⊕ < R p < 4 R ⊕ ) have been detected up to now, only ∼40 of them are orbiting around bright stars (K < 10 mag). With K = 7.15 mag, HD 183579b is hosted by the fifth brightest star among them (HD 21749b, Dragomir et al 2019;Trifonov, Rybizki & Kürster 2019;Gan et al 2021;GJ 436b, Butler et al 2004;Knutson et al 2011;HD 95338b, Díaz et al 2020;and HD 3167c, Vanderburg et al 2016;Livingston et al 2018), making it an excellent target for future atmospheric characterization using the upcoming James Webb Space Telescope (JWST, Gardner et al 2006) and Extremely Large Telescope (ELT, Gilmozzi & Spyromilio 2007;de Zeeuw, Tamai & Liske 2014).…”
Section: Atmospheric Characterization Of Hd 183579bmentioning
confidence: 99%
“…Given the brightness of HD 183579 (V = 8.7 mag), most highresolution optical spectroscopy facilities like the Planet Finder Spectrograph (PFS; Crane, Shectman & Butler 2006;Crane et al 2008Crane et al , 2010 can achieve high SNR and reach the 1 m s −1 precision. In addition, the expected rotation time-scale of HD 183579 is well separated from the planet orbital period, making it possible to smooth out the stellar activity effects in RVs with high-cadence observations (López-Morales et al 2016;Gan et al 2021).…”
Section: Prospects On Future Follow-up Observationsmentioning
confidence: 99%